WE3.1 Compliance of Prescription of Intravenous Fluid Resuscitation in Surgical Patients According to NICE Guidelines. (9th August 2022) - Morsy, Hesham; Li, Michael; Davidson, Chris; Patel, Dharti; Ali, Maryam; Hollingshead, James; Gu, Kat
Abstract: Aim: Assess compliance of prescription of for intravenous resuscitation fluids in accordance with NICE Guidelines in the acute surgical admissions population. Method: We collected data prospectively for surgical patients admitted between 25/02/21–18/03/21 (first cycle) & 12/09/2021–4/10/2021 (2nd cycle). Maximum of 5 patients daily randomly selected. Data collected on wards after clerking on Day 1 of admission. Surgical Proforma was used to identify time of admission, presenting history and co-morbidities of patients. NEWS Charts used to identify observations of patients on admission. Drug charts used to assess volume and types of intravenous fluids prescribed. Admissions by audit authors were excluded to prevent selection bias. Intervention: Posters in Emergency Assessment Unit and Wards, Teaching to junior doctors, Regular reminder messages to on-call teams. Results: 72 patients included in audit. Prescription of Intravenous resuscitation fluids in Acute Surgical Patients in compliance with NICE guidelines rose from 49% to 69% between cycle 1 and 2, respectively. Correct prescriptions in volume and type of fluid rose from 2% (cycle 1) to 44% (cycle 2). Conclusions: Almost one third of acute admissions met the criteria for resuscitation IV fluids. In indicated patients, nearly one half of patients were correctly prescribed resuscitation fluids in accordance with guidelines.